1970
DOI: 10.1111/j.1939-0025.1970.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive growth in preschoolers through verbal interaction with mothers.

Abstract: General and verbal IQ's of three groups of low‐income preschoolers were compared before and after exposure of the Experimental group to seven months of Home Sessions stimulating verbal interaction in mother‐child dyads. The Experimental group made highly significant cognitive gains in contrast to the two Comparison groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

1973
1973
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(36 citation statements)
references
References 8 publications
0
34
0
2
Order By: Relevance
“…He further suggests that parents not only reinforce the effects of the program while it is operational but also contribute to sustaining positive effects after it ends. More and more evidence (Gordon, 1971;Levenstein, 1970;Klaus and Gray, 1968;Gilmer et al, 1970;Karnes et al, 1969) has been reported to support the importance of involving parents in the education of their young children.…”
Section: Working Wi1h Paren1s On Fhe Itnumentioning
confidence: 93%
“…He further suggests that parents not only reinforce the effects of the program while it is operational but also contribute to sustaining positive effects after it ends. More and more evidence (Gordon, 1971;Levenstein, 1970;Klaus and Gray, 1968;Gilmer et al, 1970;Karnes et al, 1969) has been reported to support the importance of involving parents in the education of their young children.…”
Section: Working Wi1h Paren1s On Fhe Itnumentioning
confidence: 93%
“…They have been taught what to teach their children and they have been considered as the vehicle of intervention. Although exceptions exist (Boger, Richter, & Weatherston, 1983;Bromwich, 1981;Bromwich & Parmelee, 1979;Gordon, 1969Gordon, , 1973Levenstein, 1970;Weikart & Lambie, 1969), little emphasis has been placed on the parent-child relationship, on the parents as important attachment-affectional figures, and on the parents' own needs as individuals. This oversight in the field is of particular significance in light of the overpowering evidence in the developmental literature in support of the importance of positive parent-child interactions for the optimal development of both normal and handicapped infants (Adelson & Fraiberg, 1974;Beckwith, Cohen, Kopp, Parmelee, & Marcy, 1976 & Beckwith, 1979;Field, 1977;Goldberg, 1979;Jones, 1979;Lewis & Rosenblum, 1974;Lytton, 1980;Stern, 1974;Tronick, Adamson, Wise, Als, & Brazelton, 1978).…”
Section: The Transactional Model Of Early Home Inter Ventionmentioning
confidence: 99%
“…But for satisfactory results in the long-term, parental co-operation is essential. Since 1968 five independent studies have demonstrated the significance of the mother's role in the child's development (Hess & Shipman, 1968;Klaus & Grey, 1968;Gordon, 1969;Karnes et al 1970;Levenstein, 1970). When mothers had been instructed in the principles of child development and in the use of toys and other materials, their children showed a marked improvement in I.Q.…”
Section: Parental Co-operationmentioning
confidence: 99%